Jean-Jacques Rousseau and the Crisis of Theodicy - Pieniążek, Paweł (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The aim of the article is to present the crisis of theodicy as a source of the birth of the modern idea of history; history and its evil cannot be explained through the categories of theodicy, although in Rousseau, history offers a solution, which at the same time it negates. Later the text analyses the problems and difficulties associated with the idea of history in Rousseau, as well as presenting an attempt to verify O. Marquardt’s thesis relating to autonomisaton (of man and history) in the light of H. Blumenberg’s conception.